2018
DOI: 10.3892/mmr.2018.8416
|View full text |Cite
|
Sign up to set email alerts
|

miR‑98‑5p promotes osteoblast differentiation in MC3T3‑E1 cells by targeting CKIP‑1

Abstract: Casein kinase 2-interacting protein 1 (CKIP-1) is a negative regulator for bone formation. Previously, using bioinformatics analysis, CKIP‑1 has been predicted to serve the role of target gene of miR‑98‑5p. In the present study, the potential role of miR‑98‑5p in regulating osteoblast differentiation through CKIP‑1 was investigated. Following pre‑treatment with microRNA (miR)‑98‑5p agomir or miR‑98‑5p antagomir, MC3T3‑E1 cells were cultured in an osteoinductive medium. Subsequently, the expression of miR‑98‑5p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
2
10
1
Order By: Relevance
“…Xi et al reported that the AKT/mTOR signaling pathway participates in the inhibition of osteoporosis by promoting osteoblast proliferation, differentiation and bone formation in vitro and in vivo models [29]. In this study, we found that overexpression of CKIP-1 significantly inhibits the AKT/mTOR pathway, while OGY treatment reactivates the inhibited AKT/mTOR pathway, which is consistent with previous studies [9,[30][31][32][33][34][35]. Therefore, CKIP-1 acts as an intermediary between QGY and AKT/mTOR signaling crosstalk.…”
Section: Discussionsupporting
confidence: 93%
“…Xi et al reported that the AKT/mTOR signaling pathway participates in the inhibition of osteoporosis by promoting osteoblast proliferation, differentiation and bone formation in vitro and in vivo models [29]. In this study, we found that overexpression of CKIP-1 significantly inhibits the AKT/mTOR pathway, while OGY treatment reactivates the inhibited AKT/mTOR pathway, which is consistent with previous studies [9,[30][31][32][33][34][35]. Therefore, CKIP-1 acts as an intermediary between QGY and AKT/mTOR signaling crosstalk.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, WNT5A was significantly up-regulated with log2 fold change 1.60 and p value 4.47 × 10 −4 , which was in accordance with the results that when the cartilage was damaged, miR-92a-3p repressed the chondrogenic differentiation and reduced cartilage matrix synthesis by enhancing the expression of WNT5A [41]. MiR-98-5p is involved in the regulation of osteoblast differenti- ation and promotes its differentiation through targeting and regulating CKIP-1 expression [42].…”
Section: Discussionsupporting
confidence: 86%
“…MiR-1-3p (Zhou et al, 2020) directly targeted and inhibited the expression of hypoxia-inducible factor 1-alpha inhibitor (HIF1AN), miR-5100 (Wang et al, 2017) directly inhibited the expression of Tob2, miR-7-5p (Chen B. et al, 2018) directly targeted chemokine-like receptor 1 (CMKLR1), miR-590-3p (Wu S. et al, 2016) directly inhibited the expression of adenomatous polyposis coli (APC), and miR-98 promoted osteogenic differentiation via targeting HMGA2 in human BMSCs (Gao et al, 2018). Liu et al (2018) Interestingly, in one study, miR-98-5p negatively regulated the expression of casein kinase 2 interacting protein-1 (CKIP-1) gene and protein to promote the osteogenic differentiation of MC3T3-E1 cells (Liu et al, 2018). But another study in three types of cells (MC3T3-E1 cells, mouse and human BMSCs), miR-98-5p inhibited osteogenic differentiation by targeting HMGA2 (Zheng et al, 2019).…”
Section: Mirnas Regulate Other Factors In Osteoblastsmentioning
confidence: 99%